A new gigantopterid genus from the late Permian of the Daha Coalfield, Tibetan Plateau and its implication on plant-insect interactions. (2nd December 2021) - Zhou, Wei-Ming; Chen, Bi-Yun; Sun, Wei; He, Xue-Zhi; Hilton, Jason; Wang, Jun
ABSTRACT: Gigantopterid plants share common traits of megaphyllous leaves with multi-ordered venation and have a stratigraphic distribution restricted to the Permian Period. They display a large variety of leaf morphologies which may indicate affinities from more than one plant groups including ferns and pteridosperms such as the peltasperms. Here we describe a new genus of gigantopterid with two species from the upper Permian Nayixiong Formation in the Daha Coalfield, Qinghai Province, China. The new genus Filigigantopteris is markedly different from other gigantopterid genera in having fern-like leaf architecture with double-meshed venation. Filigigantopteris asymmetrica gen. et sp. nov. is characterised by its asymmetric pinnules with dissected lobes, while Filigigantopteris dahaia gen. et sp. nov. is characterised by its once-pinnate frond. A gigantopterid leaf figured from the Lopingian of southwest China that was previously incorrectly assigned to Gigantopteris nicotianaefolia may represent a third species of Filigigantopteris . The new genus further emphasises the morphological diversity and obscure systematic position of the Permian gigantopterids. In addition, three types of functional feeding groups, including hole feeding, margin feeding and probably skeletonisation, are present on laminae of Filigigantopteris, suggesting frequent and diverse plant-insect interactions between gigantopterid megaphylls and herbivorous insects in Cathaysia.